Capturing hydrological connectivity structure of wetlands with indices based on graph theory: A case study in Yellow River Delta. (1st December 2019) - Liu, Jiakai; Engel, Bernard A.; Dai, Liyi; Wang, Yu; Wu, Yanan; Yan, Guoxin; Cong, Ling; Zhai, Jiexiu; Zhang, Zhenming; Zhang, Mingxiang
Abstract: Coastal wetlands, greatly influenced by hydrological processes, are highly productive ecosystems but have suffered serious degradation in many locations. Hydrological connectivity frameworks provide a new perspective to study both hydrological behavior and the relationship between hydrological and ecological processes. Although some indices have been developed to parameterize hydrological connectivity structure (HCS) in different environments, the indices only consider soil water content (SWC) or topography and are limited in some specific areas. Due to its importance to understand ecological-hydrological interaction and wetland conservation and restoration. There is still a necessity to develop indices to capture hydrological attributes. In the current study, we collected soil-hydrological data in the Yellow River Delta and three indices, main flow direction (TM) based on topography, over field capacity index (OFCI) based on SWC, and topographic over field capacity index (TOFCI) based on both topography and SWC are developed using graph theory. The results show OFCI in a semi-artificial pond is significantly higher than in intertidal flats, tidal marshes and riverside wetlands, and TOFCI values in four wetland types differ significantly. TM does not show statistical differences for wetland types explored. According to the parameterized values, the semi-artificial pond has the strongest HCS, followed by intertidal flats. Tidal marshes and riverside wetlands have the weakest HCS. The landscapes of different wetland types are related to the HCS on the surface soil layer, and four wetland types in the Yellow River Delta can be distinguished by TOFCI values. The results also indicate that TOFCI can be used to locate degraded wetland areas for restoration, however more specific relationships between HCS indices and ecological structure are desirable in the future.